A Case of Toxic Breast-feeding?. Issue 1 (January 2019) - Schultz, Megan L.; Kostic, Mark; Kharasch, Sigmund
Abstract : Abstract: Opiates are frequently prescribed postpartum for pain relief after cesarean delivery, episiotomies, and headaches. It is estimated that greater than 30% of breast-feeding mothers in the United States are prescribed opiates for pain relief associated with childbirth. Many opiates are readily transferred to human milk, although life-threatening events are rare. We report a 6-day-old breast-feeding infant whose mother was taking hydromorphone for pain relief from a cesarean delivery and whose clinical course was suggestive of opiate toxicity. This case emphasizes the importance of thorough medication history taking in postpartum breast-feeding mothers whose infants may present with symptoms of opiate toxicity. Semisynthetic opiates are frequently not detected on emergency department urine toxicology screens. The pertinent literature is reviewed.